Measuring the New Indices of Religious Orientation at the cathedral carol service: internal consistency and reliability among a distinctively wide ranging sample - Walker, David (Journal of beliefs and values, 2012)
The New Indices of Religious Orientation (NIRO) proposed and tested by Francis have been found in later studies to satisfy the requirements for internal reliability among samples where there are comparatively high levels of religious activity, and usually of predominantly older adults. The present study takes a sample of 393 individuals who attended Christmas Carol Services in Worcester in 2009. The sample was found to contain both a majority with quite low levels of churchgoing frequency and a much higher proportion of younger adults than in other studies of churchgoers. All the indices achieved satisfactory alpha coefficients (intrinsic 0.91, extrinsic 0.73, quest 0.80) with the item-rest of test scores being above 0.28 in all cases. It is concluded that the NIRO indices are likely to be a useful tool for analysing religious orientation and motivation among samples with relatively low or wide-ranging levels of religious practice and with a wide age range. The ‘compartmentalisation’ subsection of the extrinsic scale is identified as perhaps being considered for some refinement.